Capital Theory and Effective Demand**. (28th April 2022) - Bhaduri, Amit
Abstract: Using simple national income accounting and a fixed coefficient two sector model this paper examines how the problem of capital valuation upsets the foundations of the marginal productivity theory of distribution. Assuming no capital valuation problem and zero Wicksell effect, both marginalist theory and the labour theory of value hold. However, the same equation that makes the Wicksell effect zero also entails the profit realization condition of effective demand for the 'golden age'. This argument is extended providing a new perspective to the link between effective demand and capital theory.